2020
DOI: 10.1021/acsapm.0c00235
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Stimuli-Responsiveness Fluorescent Probe Derived from Cyclopolymers and Pyrene-Ended Ammonium Salts

Abstract: A multiple stimuli-responsiveness fluorescent probe was fabricated by host-guest recognition between cyclopolymers with larger pseudocrown ether cavities in the backbones and pyrene-ended ammonium salts. Also, this fluorescent probe exhibits ratiometric responsiveness to chloride anions, organic bases, and temperature, as well as a dual luminescence responsiveness to nitro-compounds. These properties of this probe endow it with potential application in multiple stimuliresponsive chemical fluorescence sensors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Based on their amphiphilic nature of supra-amphiphiles (WP[6]@Cb-BA), supramolecular prodrug self-assemblies (SPSAs-1) can be further obtained. Utilizing pyrene as the fluorescent probe, 30 the critical aggregation concentration (CAC) was first measured to prove the formation of SPSAs-1 (Fig. S11, ESI †).…”
Section: Construction Of Wp[6]-based Supramolecular Self-assembliesmentioning
confidence: 99%
“…Based on their amphiphilic nature of supra-amphiphiles (WP[6]@Cb-BA), supramolecular prodrug self-assemblies (SPSAs-1) can be further obtained. Utilizing pyrene as the fluorescent probe, 30 the critical aggregation concentration (CAC) was first measured to prove the formation of SPSAs-1 (Fig. S11, ESI †).…”
Section: Construction Of Wp[6]-based Supramolecular Self-assembliesmentioning
confidence: 99%
“…The maleic anhydride moieties of thus-obtained alternating cyclocopolymers were transformed via hydrolysis, alcoholysis, or aminolysis toward hydrosphere material applications such as a biopharmaceutical 45,46 and a fluorescent sensor for metal ions. 44,47,48 N-Substituted maleimide derivatives (MIs) are the alternative comonomers of maleic anhydride, but there have been not so many attempts on the alternating copolymerization of VEs with MIs. 49−53 We intentionally focused on MI as an electron-poor comonomer toward tuning of the physical properties via design of the MI pendant group.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A few examples have been reported on such peculiar cyclopolymerizations of vinyl ether- or styrene-based divinyl monomers, such as divinyloxyethylene (CH 2 =CH–O–CH=CH 2 ) and distyrenes linked by a pseudo-crown ether spacer or pseudo-cryptand spacer, in conjunction with maleic anhydride as a comonomer. The maleic anhydride moieties of thus-obtained alternating cyclocopolymers were transformed via hydrolysis, alcoholysis, or aminolysis toward hydrosphere material applications such as a biopharmaceutical , and a fluorescent sensor for metal ions. ,, N -Substituted maleimide derivatives (MIs) are the alternative comonomers of maleic anhydride, but there have been not so many attempts on the alternating copolymerization of VEs with MIs. We intentionally focused on MI as an electron-poor comonomer toward tuning of the physical properties via design of the MI pendant group. Consequently, we examined radical copolymerizations of 1 with MIs in detail to achieve syntheses of the alternating cyclocopolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescent materials have gained extensive research interest in recent years due to their widespread applications in biological sensing, 1,2 lighting devices, 3,4 stimuli-responsive materials, 5,6 and so on. 7−11 However, traditional fluorophores oftentimes suffer from aggregation-caused quenching (ACQ) effects in condensed states wherein the fluorescence would be quenched precipitously because of the exciton interactions and nonradiative decays.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fluorescent materials have gained extensive research interest in recent years due to their widespread applications in biological sensing, , lighting devices, , stimuli-responsive materials, , and so on. However, traditional fluorophores oftentimes suffer from aggregation-caused quenching (ACQ) effects in condensed states wherein the fluorescence would be quenched precipitously because of the exciton interactions and nonradiative decays. , This issue was subtly addressed when Tang et al reported a completely opposite phenomenon known as aggregation-induced emission (AIE). In such cases, certain fluorogens that emit weakly in dilute solution become highly emissive in the aggregated state on account of the restriction of intramolecular rotation (RIR) …”
Section: Introductionmentioning
confidence: 99%